Patrick Sériot, Elena Bulgakova, Andreja Eržen. Folk Linguistics and Pseudo-Scientists. Translated by Vilhelmina Vitkauskienė - Vitkauskienė, Vilhelmina (Respectus Philologicus, 2015)
Original article: La linguistique populaire et les pseudo-savants.
Keywords: none